Software quality assurance in large scale and complex software-intensive systems - Mistrík, Ivan; Soley, Richard Mark; Ali, Nour; Grundy, John; Tekinerdogan, Bedir (Morgan Kaufmann, 2016)
Software Quality Assurance in Large Scale and Complex Software-intensive Systems presents novel and high-quality research related approaches that relate the quality of software architecture to system requirements, system architecture and enterprise-architecture, or software testing. Modern software has become complex and adaptable due to the emergence of globalization and new software technologies, devices and networks. These changes challenge both traditional software quality assurance techniques and software engineers to ensure software quality when building today (and tomorrow's) adaptive, context-sensitive, and highly diverse applications. This edited volume presents state of the art techniques, methodologies, tools, best practices and guidelines for software quality assurance and offers guidance for future software engineering research and practice. Each contributed chapter considers the practical application of the topic through case studies, experiments, empirical validation, or systematic comparisons with other approaches already in practice. Topics of interest include, but are not limited, to: quality attributes of system/software architectures; aligning enterprise, system, and software architecture from the point of view of total quality; design decisions and their influence on the quality of system/software architecture; methods and processes for evaluating architecture quality; quality assessment of legacy systems and third party applications; lessons learned and empirical validation of theories and frameworks on architectural quality; empirical validation and testing for assessing architecture quality.
Includes bibliographical references and index. - Vendor-supplied metadata
Keywords: Computer software -- Quality control; Programas para computadora; Control de calidad; Logiciels; Qualité; Contrôle; COMPUTERS / Software Development & Engineering / Quality Assurance & Testing; Computer software; Quality control; Computer Science; Engineering & Applied Sciences